The effect of passive smoking on the risk of otitis media in Aboriginal and non-Aboriginal children in the Kalgoorlie-Boulder region of Western Australia - Jacoby, P.; Coates, H.; Arumugaswamy, A.; Elsbury, D.; Stokes, A.; Monck, R.; Finucane, J.; Weeks, S.; Lehmann, Deborah (Australian Medical Association, 2008)
Objectives: To determine the risk of otitis media (OM) associated with passive smoking in young children, and any competing effect between passive smoking and childcare attendance.Design, participants and setting:Prospective cohort study of 100 Aboriginal and 180 non-Aboriginal children born in Kalgoorlie Regional Hospital between 1 April 1999 and 31 January 2003. These children underwent routine clinical examinations by an ear, nose and throat specialist up to three times before the age of 2 years, and tympanometry at routine field follow-up visits from the age of 4 months. Childrens' mothers were interviewed at 1-3 weeks postpartum to provide sociodemographic data. Main outcome measures: Associations between OM and exposure to environmental tobacco smoke (ETS) and childcare attendance. Results: 82 Aboriginal and 157 non-Aboriginal children attended for routine clinical examinations. OM was diagnosed at least once in 74% of Aboriginal children and 45% of non-Aboriginal children; 64% of Aboriginal children and 40% of non-Aboriginal children were exposed to ETS. Exposure to ETS increased the risk of specialist-diagnosed OM in Aboriginal children (OR, 3.54; 95% CI, 1.68?7.47); few attended childcare. Non-Aboriginal children exposed to ETS but not attending childcare were at increased risk of OM (OR, 1.91; 95% CI, 1.07?3.42) while those attending childcare had no increased smoking-related risk. Tympanometry was performed on 87 Aboriginal and 168 non-Aboriginal children; a type B tympanogram (suggesting fluid in the middle ear) was also associated with passive smoking in Aboriginal children. Conclusions: Reducing the exposure of children to ETS is a public health priority, especially for the Aboriginal population. A smoke-free environment will help reduce the burden of OM.